Preparation and Characterization of Biomorphic CaCO3 with Hierarchically Ordered Micro- and Nano-Structures - Ding, Ming; Ni, Na (Asian Journal of Chemistry, 2013)
Biomorphic CaCO3 with different hierarchically ordered micro- and nanostructures was fabricated using chitosan solution as soft template. Influences of Ca/Mg molar ratio and temperature on crystalline morphology of CaCO3 were investigated by XRD, FTIR and SEM. The results show that facts including temperature, the ratio of calcium to magnesium have key effect on the morphology evolution of calcium carbonate.